2021
DOI: 10.1039/d0an02063j
|View full text |Cite
|
Sign up to set email alerts
|

Portable, stable, and sensitive assay to detect phosphate in water with gold nanoparticles (AuNPs) and dextran tablet

Abstract: A novel and highly sensitive tablet-based colorimetric sensor is developed for the detection of phosphate (Pi) in drinking and surface water using mercaptoacetic acid-gold nanoparticles (MA-AuNPs). Characterization of AuNPs and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…The concentration of the AuNP-dSol colloidal solution was 8.1 nmol L –1 by means of Lambert–Beer’s law, wherein the value of ε used was 2.7 × 10 8 L mol –1 cm –1 . 42 This result demonstrated that the particles were fully dispersed, and their size was almost in the same range with AuNPs-Cit and AuNPs-dSol without any contamination as a change in size or dispersibility would change the place of the absorption maxima. 47 It is a proven fact that by increasing the particle size of nanogold, the absorption maxima move toward a higher wavelength, resulting in a bathochromic (red) shift.…”
Section: Resultsmentioning
confidence: 74%
See 3 more Smart Citations
“…The concentration of the AuNP-dSol colloidal solution was 8.1 nmol L –1 by means of Lambert–Beer’s law, wherein the value of ε used was 2.7 × 10 8 L mol –1 cm –1 . 42 This result demonstrated that the particles were fully dispersed, and their size was almost in the same range with AuNPs-Cit and AuNPs-dSol without any contamination as a change in size or dispersibility would change the place of the absorption maxima. 47 It is a proven fact that by increasing the particle size of nanogold, the absorption maxima move toward a higher wavelength, resulting in a bathochromic (red) shift.…”
Section: Resultsmentioning
confidence: 74%
“…The maximum absorption band appeared at a wavelength of 520 nm for all three samples, which is a characteristic of 13 nm AuNPs. The concentration of the AuNP-dSol colloidal solution was 8.1 nmol L –1 by means of Lambert–Beer’s law, wherein the value of ε used was 2.7 × 10 8 L mol –1 cm –1 . This result demonstrated that the particles were fully dispersed, and their size was almost in the same range with AuNPs-Cit and AuNPs-dSol without any contamination as a change in size or dispersibility would change the place of the absorption maxima .…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…Taking advantages of unique surface plasmon resonance (SPR) absorption, easy surface functionalization and variable solution colors, AuNPs have been used for colorimetric sensing in food security, environmental monitoring, and health care. 8–11 Potential applications include the determination of metal ions, 12–18 pesticide residues, 19,20 bisphenol A (BPA), 21,22 phosphate, 23 azodicarbonamide (ADA), 24 antibiotics, 25–27 adenosine and nucleic acids, 28–30 dopamine, 31 bacteria, 32,33 and virus. 34,35 …”
Section: Introductionmentioning
confidence: 99%